The effect of shift work on depression in nurses - SJ Mirmohammadi; AH Mehrparvar; A FallahMehrjerdi (طب کار)
Abstract Background: Many workers in different jobs work in shift schedules. Health care workers, especially nurses are a working group which according to the job nature always have shift work. Shift work causes different physical and mental diseases, including depression. Materials and Methods: In a cross-sectional study, 110 nurses working in SSU hospitals were surveyed in two groups: shift worker and non-shift worker. The frequency of depression was measured by means of Beck questionnaire. Frequency of depression was compared in two groups. Results: Mean Beck point for non-shift-workers and shift-workers was 10.09  6.56 and 12.67  5.86, respectively and the difference was statistically significant. Conclusion: shift work is regarded as a risk factor for inducing depression. This study showed the higher frequency of depression in shift workers comparing to non-shift-workers which most of the previous studies had shown.